Consensus analysis of the weighted corona networks - Du, Weiwei; Zhu, Jian; Gao, Haiping; Li, Xianyong (Frontiers in Physics, 2022)
This paper studies the consensus of weighted corona network G1 ◦ G2. The consensus of the networks can be measured by coherence. Firstly, the Laplacian polynomial of G1 ◦ G2 is derived by using the properties of orthogonal matri. Secondly, the relationship between the first-order coherence of e G1 ◦ G2 and G1 is deduced by using the relevant properties of determinant and the conclusion of polynomial coefficients and the principal minors of matrix. Thirdly, the join operation is introduced to further simplify the analytical formula of network coherence. Finally, a specific network example is used to verify the validity of the conclusion